2010
DOI: 10.1111/j.1365-2435.2010.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions between two meadow grasses under nitrogen and phosphorus limitation

Abstract: Summary1. Different grass species dominate grasslands fertilized with nitrogen (N) or phosphorus (P), possibly due to the impact of N : P stoichiometry on competitive interactions. How species compete for nutrients, and whether the mechanisms are similar for N and P, is still not fully understood. 2. We investigated whether the outcome of competition between Alopecurus pratensis and Agrostis capillaris depends on N : P stoichiometry, and on the ability to acquire supplied N or P. Monocultures and mixtures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
107
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 54 publications
10
107
3
3
Order By: Relevance
“…The plants were germinated from seeds 2-3 weeks prior to the experiment. In this experiment, I aimed to compare the maximal PME activities of these species, and therefore grew the plants with very little P, an excess of N, and non-limiting doses of other macro-and micronutrients (K, Ca, Mg, S, Fe, Bo, Mn, Zn, Mo and Cu; for forms and doses see (Olde Venterink and Güsewell 2010)). Thus, the pots received 0.2 mg P (total in 8 weeks applied as NaH 2 PO 4 ) and 128 mg N (applied as NaNO 3 ), yielding a N:P supply mass ratio of 640.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants were germinated from seeds 2-3 weeks prior to the experiment. In this experiment, I aimed to compare the maximal PME activities of these species, and therefore grew the plants with very little P, an excess of N, and non-limiting doses of other macro-and micronutrients (K, Ca, Mg, S, Fe, Bo, Mn, Zn, Mo and Cu; for forms and doses see (Olde Venterink and Güsewell 2010)). Thus, the pots received 0.2 mg P (total in 8 weeks applied as NaH 2 PO 4 ) and 128 mg N (applied as NaNO 3 ), yielding a N:P supply mass ratio of 640.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, root phosphatase activity increases as either soil P availability decreases or N supply increases (Li et al 1997;Hayes et al 1999;Treseder and Vitousek 2001;Phoenix et al 2004;Fujita et al 2010;Olde Venterink and Güsewell 2010). These effects can both be seen as responses to increased P limitation, since N and P are the most common growth-limiting nutrients in terrestrial ecosystems (Elser et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In the case of competition for nutrients, the superior competitor will acquire a resource from the rhizosphere more rapidly than its competing neighbours, and the total root length of the competing plants is the decisive trait to enable this (Craine et al 2005). Indeed, Olde Venterink and Güsewell (2010) recently demonstrated that this pre-emption competition mechanism was supported for two competing grass species under N limitation, but not under P limitation. Under P-limitation, traits other than root length, such as root phosphatase activity and root mortality appeared to be more important for the outcome of competition for these two grasses.…”
mentioning
confidence: 95%
“…The root systems of individual plants can be highly modified by root competition as the competition for nutrients provokes higher energy investment into roots in order to increase their density and length (Olde Venterink & Güsewell 2010). The presence of nutrient-rich patches in the soil profile may also modify the root system because roots are able to proliferate and grow preferentially into nutrient-rich patches (Robinson 1994;Forde & Lorenzo 2001;Hejcman et al 2011).…”
Section: Introductionmentioning
confidence: 99%